How are APOE4, changes in body weight, and longevity related? Insights from a causal mediation analysis - Holmes, Rachel; Duan, Hongzhe; Bagley, Olivia; Wu, Deqing; Loika, Yury; Kulminski, Alexander; Yashin, Anatoliy; Arbeev, Konstantin; Ukraintseva, Svetlana (Frontiers in Aging, 2024)
The ε4 allele of the APOE gene (APOE4) is known for its negative association with human longevity; however, the mechanism is unclear. APOE4 is also linked to changes in body weight, and the latter changes were associated with survival in some studies. Here, we explore the role of aging changes in weight in the connection between APOE4 and longevity using the causal mediation analysis (CMA) approach to uncover the mechanisms of genetic associations. Using the Health and Retirement Study (HRS) data, we tested a hypothesis of whether the association of APOE4 with reduced survival to age 85+ is mediated by key characteristics of age trajectories of weight, such as the age at reaching peak values and the slope of the decline in weight afterward. Mediation effects were evaluated by the total effect (TE), natural indirect effect, and percentage mediated. The controlled direct effect and natural direct effect are also reported. The CMA results suggest that APOE4 carriers have 19%–22% (TE p = 0.020–0.039) lower chances of surviving to age 85 and beyond, in part, because they reach peak values of weight at younger ages, and their weight declines faster afterward compared to non-carriers. This finding is in line with the idea that the detrimental effect of APOE4 on longevity is, in part, related to the accelerated physical aging of ε4 carriers.